A dispersive solid-phase extraction method for the determination of Aristolochic acids in Houttuynia cordata based on MIL-101(Fe): An analytes-oriented adsorbent selection design. (1st May 2023) - Cheng, Rui; Mao, Xuejin; Yu, Jiaying; Liu, Fan; Guo, Lan; Luo, Dongmei; Wan, Yiqun
Highlights: MIL-101(Fe) was selected as a new sorbent for AA detection in Houttuynia cordata by an analytes-oriented considering. The adsorption interactions between MIL-101(Fe) and AA-I & AA-II were studied. Quantum chemical calculation and XPS spectrum were introduced into the adsorption mechanism investigation. Quantification limits were lower than allowable limit stipulated by Chinese Pharmacopoeia. Abstract: In view of the molecular structure of Aristolochic acid I (AA-I) and Aristolochic acid II (AA-II), MIL-101(Fe) was selected as the sorbent to develop a dispersive solid-phase extraction (d-SPE) method for capturing the two analytes from Houttuynia cordata. The interactions between the sorbent and analytes were investigated by FT-IR, XPS and UV–Vis DRS spectra. The optimized method demonstrated good linearity with R 2  > 0.9999. The limit of detections (LODs) were 0.007 mg/L and 0.014 mg/L for AA-I and AA-II, respectively, lower than the limit stipulated by Chinese Pharmacopoeia (0.001 %, w/w). The recoveries for AA-I and AA-II were within the range of 73.3–106.4 %. The precisions of intra-day and inter-day were 0.9–5.8 % and 2.1–5.8 %, respectively. Thus, the established method demonstrated to be efficient and reliable to determine AA-I and AA-II in Houttuynia cordata.